(untitled) (Research, Society and Development, 2025)
The inadequate management of swine fecal waste endangers human health and the environment, causing soil contamination, the spread of zoonoses, and eutrophication of water bodies. These nutrient-rich wastes also contain antibiotic resistance genes (ARGs), posing a significant public health risk. This systematic review aims to identify optimal operating parameters for stabilizing pig waste, focusing on the production of compost, biosolids and biogas, while taking into account the specific composition of these wastes. Operational parameters for waste stabilization, including composting, and biogas generation, are analyzed. The findings aim to identify issues and propose solutions for a more sustainable and efficient management of these wastes, thereby protecting the environment and public health.